2004
DOI: 10.1590/s0100-879x2004000400009
|View full text |Cite
|
Sign up to set email alerts
|

Trends in drug use among students in Brazil: analysis of four surveys in 1987, 1989, 1993 and 1997

Abstract: The consumption of psychotropic drugs among Brazilian secondary school students was examined by comparing data from four surveys using a questionnaire adapted from the WHO's Program on Research and Reporting on the Epidemiology of Drug Dependence. Students filled out the form in their classrooms without the presence of teachers. The target population consisted of 10-18-year-old students (on average, 15,000 students responded to each survey) in Brazil's ten largest state capitals: Belém, Belo Horizonte, Brasíli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
38
1
33

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(76 citation statements)
references
References 15 publications
4
38
1
33
Order By: Relevance
“…22 A survey conducted in 10 Brazilian capitals found that the frequent use of alcohol (six or more times per month) in students aged 10 to 18 years increased from 9.2%, in 1987, to 15%, in 1997. 9 Although the literature points out that single, divorced, or widowed people generally consume more alcohol, 2,11,17,25 the present study did not fi nd any association between marital status and alcoholism.…”
Section: Discussioncontrasting
confidence: 66%
“…22 A survey conducted in 10 Brazilian capitals found that the frequent use of alcohol (six or more times per month) in students aged 10 to 18 years increased from 9.2%, in 1987, to 15%, in 1997. 9 Although the literature points out that single, divorced, or widowed people generally consume more alcohol, 2,11,17,25 the present study did not fi nd any association between marital status and alcoholism.…”
Section: Discussioncontrasting
confidence: 66%
“…Data from the Brazilian population show an increase in consumption of appetite suppressants from 2001 to 2005, as previously reported among middle and high school students from 1987 to 2004. 4 These students seem to consume alcohol, tobacco, marijuana, hallucinogens and synthetic drugs more often than Brazilian college students in general. h Both experimentation and regular use of alcohol seem to have reached a ceiling, particularly among Biological Sciences and Arts & Humanities students.…”
Section: Discussionmentioning
confidence: 98%
“…No Brasil, levantamentos sistemáticos têm sido realizados com o objetivo de estudar a prevalência do uso de álcool e outras drogas [1][2][3][4][5][6] . No último Levantamento Domiciliar, realizado em 2005, o uso na vida de drogas ilícitas foi referido por 22,8% dos entrevistados, prevalecendo o uso de maconha (8,8%) e solventes (6,1%).…”
Section: Introductionunclassified
“…Além do crescente consumo, estudos apontam significativa diferença do uso de drogas entre os sexos. Indivíduos do sexo masculino, em geral, utilizam mais álcool ou outras drogas, revelando um importante padrão social do consumo dessas substâncias 3,[6][7][8] .…”
Section: Introductionunclassified
See 1 more Smart Citation